Analisis Akustik Ruang Vokal Kanak-Kanak Melayu (Jurnal Bahasa, 2011)
Research was conducted to explore the acoustic vowel space of normal Malay children age one to four year olds. Eight children were selected and divided into four groups of two. Two adults were also selected as subjects for the study. All subjects were from Kula Lumpur. Speech samples were recorded using a digital audio recorder and analysed by using PRAAT software. Values of first formant (F1) and second formant (F2) which were extracted from the acoustic analysis were plotted on graphs. Six Malay vowel /a,i,u,e,o,´/ were identified and elaborated. The development of and changes in vowel spaces for each age group were described. The resulting data was examined in relation to vocal tract physiology as well as the age of the subjects. Comparison was also made between the vowel space of children and adults. The study showed that the pattern of vowel spaces and the position of each vowel in terms of vowel space changes as children grow. However, the results also show that the height and width of vowel spaces do not change in a linear manner as children’s age increases.